OSL dating of coastal dunes on the southeastern coast of Hainan Island, China - Zhou, Liang; Yang, Yang; Li, Gaocong; Tong, Changliang (Frontiers in Marine Science, 2023)
Coastal dune sediments and landforms offer a unique opportunity to understand climate change and sea level change on the centennial-millennial time scale. However, there is a paucity of chronological studies on the effects of storms on the evolution of coastal dunes along the temperate coastline of China. In this study, optically stimulated luminescence (OSL) dating of sand dunes was conducted to investigate the process and mechanism of coastal dune evolution on the southeastern coast of Hainan Island, China. The results show that the coastal dune evolution experienced three rapid accumulation periods: 28-21 ka, 14-4 ka, and 3.0 ka-present. The three rapid accumulation periods correspond to the last glacial maximum, the late Pleistocene/early-mid Holocene, and the late Holocene climatic dry-cold period, respectively. Sea level change and the East Asian winter monsoon, in conjunction with the enhanced storminess, play a key role in driving the sand dune evolution on the south-eastern coast of Hainan Island. These findings are of great significance for regional planning and coastal defense schemes.